Condiciones de vida y trabajo de familias campesinas agricultoras de Marinilla, un pueblo agrario del oriente Antioqueño, Colombia, 2011 (2013)
ABSTRACT: To describe the socio-economic, health, hygienic, sanitary and working conditions of farming families living in the municipality of Marinilla, Antioquia. Methodology: a cross-sectional descriptive study conducted with a nonrandom sample of 83 families. The goal was reached by applying a questionnaire and observing the hygienic and sanitary conditions of the houses in nine villages. Results: the type of agriculture observed was family farming. The farming activities were performed in the participants’ property and did not generate enough income to survive (73.8%). Similarly, these activities were performed using hand tools (99%) and the only equipment available were fumigation pumps (79.1 %). Although agriculture has covered the life and generational cycles of the family members, only 17.7% of them want their children to carry on with the agricultural tradition. Work was performed in shifts of 8 or more hours, 6 or 7 days a week, with no holidays, with an accident rate of 26.2%, with continuous use of pesticides of moderate to high hazard for 25.9 years on average and with low (3.9%) social protection covering incapacity, disability, old age and death. However, this study identified increases in land ownership (65%), affiliation to the subsidized health system (96.3%), level of literacy -although the level of technical or professional higher education was 3.2%- and access to the communal water supply (96.4%). Conclusion: agriculture continues to play a key role in the Marinilla country life, and there is little hope for the coming generations; regional leaders must act effectively if they want to preserve the agricultural district of Eastern Antioquia.